Exploring Pain Distribution: Unveiling Lower Back Pain As The Prominent Player - Novy, Theresia Chandra Tania; Mogi, Theresia Isye; Yaputri, Maria Jessica (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Pain is a significant health issue affecting millions worldwide, with lower back pain being particularly prevalent. A comprehensive understanding of pain distribution across different body regions is essential for effective management, yet studies on this in clinical settings are limited. Aim(s): This study aimed to evaluate the prevalence and distribution of pain among patients at a pain clinic, focusing on identifying the most affected body regions and the impact of chronic conditions and comorbidities. Material and methods: A descriptive study conducted at Bandung Pain & Rehab Center from January 2019 to December 2022 included 5,103 subjects from 5,139 medical records. Demographic and clinical characteristics were analyzed using univariate analysis, revealing distinct chronic pain subgroups based on intensity, quality, clinical outcomes and comorbidities. Result: The study included 435 patients, with a higher prevalence of pain observed in females (59.8%) compared to males (40.2%). Lower back pain was the most frequently reported issue, affecting 58.2% of patients, followed by neck pain (24.4%) and shoulder pain (17.4%). Chronic pain was reported in 76.1% of patients, with the majority experiencing pain for more than six months. Comorbidities, including diabetes and hypertension, were found in 38.4% of patients, significantly influencing pain severity and distribution. Conclusions: Lower back pain emerges as the most prevalent pain condition among patients in this study, highlighting the need for focused interventions in this area. The association between chronic pain and comorbidities underscores the importance of comprehensive pain management strategies that consider the patient's overall health. These findings can guide clinicians in developing more effective treatment plans and improve patient outcomes in pain management.